Calculation of the stress-strain state of complex reinforced metal-composite shells under steady-state creep conditions - Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2011)
This paper presents a formulation of the problem of deformation of variable thickness shells reinforced by fibers of constant cross-section. All components of these metal-composite shells operate under steady-state creep conditions. The system of resolution equations together with the appropriate boundary conditions is analyzed. A method for the solution of the problem formulated here is developed. The way to get the approximate solution to the problem at the first stage of unsteady-state creep is proposed. Calculations performed for cylindrical shells indicate that the compliance of such structures under steady-state creep conditions depends strongly on the reinforcement structure.